Fasting stress hyperglycemia ratio as a predictor of intramyocardial hemorrhage and adverse outcomes in ST-segment elevation myocardial infarction - Zhao, Hang; Tao, Zhengyu; Wang, Xu; Li, Xinli; Chang, Hao; Ji, Ding-Kun; Xia, Weiliang; Jiang, Meng; Pu, Jun (Frontiers in Endocrinology, 2026)
IntroductionIntramyocardial hemorrhage (IMH) represents the most severe form of microvascular injury and is associated with poor prognosis in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PPCI). However, the associations of glycemic parameters with the occurrence of IMH remain unclear. We aimed to evaluate the association of fasting stress hyperglycemia ratio (SHR)—a novel metric that adjusts acute glucose for chronic glycemia—with the presence of IMH and to explore its relationship with clinical outcomes in patients with STEMI.MethodsThis study utilized data from the prospective, multicenter EARLY-MYO-CMR registry (NCT03768453). We enrolled consecutive STEMI patients undergoing PPCI who had cardiac magnetic resonance (CMR) imaging within a week after the index infarction. The primary endpoint was the presence of IMH defined by CMR T2* mapping. A secondary clinical endpoint was the composite of major adverse cardiac events (MACE) during follow-up.ResultsAmong the 496 patients included in this study, 205 (41.3%) exhibited IMH. Multivariable analysis identified fasting SHR as the strongest independent predictor of IMH (adjusted odds ratio [aOR] per 0.1-unit increase: 1.21; 95% CI: 1.10–1.33, P<0.001), outperforming fasting blood glucose and HbA1c. This association was consistent in both non-diabetic (aOR: 1.27; P=0.001) and diabetic patients (aOR: 1.21; P=0.015). Restricted cubic spline analysis revealed a significant nonlinear relationship (P for nonlinearity=0.004), characterized by a rapid increase in IMH risk at lower SHR levels, where the study population was primarily concentrated, and remained consistently high thereafter. During a median follow-up of 25 months, elevated fasting SHR was significantly associated with an increased risk of MACE (Unadjusted hazard ratio per 0.1-unit increase: 1.20; 95% CI: 1.11–1.31; P<0.001; adjusted hazard ratio per 0.1-unit increase:1.20; 95% CI: 1.09–1.31; P<0.001), with Kaplan-Meier analysis confirming a significantly higher cumulative incidence of MACE in the high SHR group (log-rank P<0.001).DiscussionFasting SHR was a potent, independent predictor of IMH in reperfused STEMI. Notably, the IMH risk escalates rapidly even at lower SHR levels, underscoring the critical need for early management of stress hyperglycemia. Elevated SHR was significantly associated with increased risk of MACE. These findings establish fasting SHR not only as a biomarker for microvascular injury but also as a pivotal tool for early risk stratification in STEMI.